Bruchidius marginalis (Fabricius, 1776) (Coleoptera: Chrysomelidae: Bruchinae) – a species new to the Republic of Khakassia (Russia) - Lopatina, Sofia V. (Acta biologica sibirica)
Bruchidius marginalis, a seed beetle, is found in various countries, the including the Baltic countries, Balkan peninsula, central, northern, and the western Europe, and Transcaucasian countries. In Russia, the species was previously noted in the south of its European part, Saratov and Kaliningrad regions. Oxytropis pilosa, a South Palearctic species, grows in central Europe, the European part of Russia, the Caucasus, Siberia, Mongolia, and Asia Minor. It is distributed in the steppe zone, insular steppes, forb and forb-grass steppes, and steppe meadows. A count of damaged O. pilosa seedlings was made and the percentage of fruit infection by seed-eating insects was calculated. The level of infestation in the O. pilosa fruits was 23%, and mass emergence of adults was observed in September. When examining leguminous plants for infection with seed-eating insects, a species of carpophage Bruchidius marginalis was identified, which is the first for the territory of the Republic of Khakassia.